The Pengaruh Brand Ambassador Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Produk Air Minum Dalam Kemasan (Amdk) Le Minerale - Lesmana, Mochamad Al Fachry; Handayani, Rini (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the influence of Brand Ambassador and Consumer Confidence on Purchasing Choices of Le Minerale AMDK Products in the Parongpong District, West Bandung Regency. The methodology used in this study is descriptive and associative with data collection through questionnaires. The results of the descriptive analysis indicate that the Le Minerale Brand Ambassador is included in the good category, but still needs improvement in terms of selecting brand ambassador figures who are more capable of expressing and implementing a healthy lifestyle to attract more consumers. Consumer Trust in Le Minerale is also classified as good, although it has not yet been fully able to provide a sense of trust from the public to use the product. On the other hand, Consumer Purchasing Decisions for Le Minerale products are also stated to be good, although there are still some consumers who do not always choose this product because of the presence of other AMDK brands that are more preferred by the public. The associative analysis shows that the Brand Ambassador has a significant positive influence of 22.2% on Purchasing Choices. In addition, Consumer Confidence also has a significant positive influence of 41.5% on Purchasing Choices. Simultaneously, Brand Ambassador and Consumer Confidence contributed positively and significantly by 63% to the Purchase Choice of Le Minerale AMDK products among the people of Parongpong District, West Bandung Regency.